Comprehensive Transcriptomic and Proteomic Profiling of CILD40 with Novel Compound Heterozygous Mutations of DNAH9 - Siming Kong; Mingshuo Wang; Xuedong Wang; Yakun Liu; Pengfei Wang; Wenyan Song; Ziye Chen; Yuxin Su; Canhong Xiang; Yunfang Wang; Hui Bai (Phenomics, 2026)
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterized by impaired ciliary motility that leads to respiratory symptoms, laterality defects, and other systemic abnormalities. Despite significant advancements in genetic research identifying over 50 causative genes and enabling genetic diagnosis in approximately 90% of cases, comprehensive phenotypic characterization remains underexplored. We investigated two respiratory asymptomatic individuals (sisters) who exhibited laterality defects in a three-generation family, both of whom harbored novel compound heterozygous mutations (NM_001372.4:c.308del and NM_001372.4:c.11845G > A) in the dynein axonemal heavy chain 9 ( DNAH9 ) gene associated with primary ciliary dyskinesia-40 (CILD40). Structural modeling and western blotting analysis of HEK-293T cells demonstrated that the frameshift mutation abolished DNAH9 stability, whereas the missense mutation disrupted hydrogen bonds, leading to partial protein destabilization. Peripheral blood RNA sequencing revealed extensive dysregulation of axonemal and intraflagellar transport genes, implicating defects in microtubule-based motility in the two affected siblings with biallelic DNAH9 mutations, but not in their heterozygous family members or one unaffected relative. Plasma proteomic analysis of patients with CILD40 identified significant enrichment of pathways related to platelet activation, complement and coagulation cascades. Further comparative analysis with a patient with PCD caused by a CCDC40 mutation (CILD15 subtype) revealed differential signatures in CILD40, highlighting the potential of plasma proteomics for understanding distinct pathogenic mechanisms across PCD subtypes. These findings underscore the critical role of DNAH9 compound heterozygous mutations in CILD40 and provide new insights into the genetic, transcriptional, and proteomic phenotypic heterogeneity of PCD.